Genetic Mapping and Confirmation of Quantitative Trait Loci for Seed Protein and Oil Contents and Seed Weight in Soybean. Issue 3 (1st May 2013) - Pathan, Safiullah M.; Vuong, Tri; Clark, Kerry; Lee, Jeong‐Dong; Shannon, J. Grover; Roberts, Craig A.; Ellersieck, Mark R.; Burton, Joseph W.; Cregan, Perry B.; Hyten, David L.; Nguyen, Henry T.; Sleper, David A.
ABSTRACT: Demand for soybean [ Glycine max (L.) Merr.] meal has increased worldwide and soybean importers often offer premiums for soybean containing higher contents of protein and oil. Objectives were to detect quantitative trait loci (QTL) associated with soybean seed protein, oil, and seed weight in a soybean mapping population and confirm detected QTL across genetic backgrounds and environments. Two populations of 216 and 156 recombinant inbred lines were developed from Magellan × PI 438489B and Magellan × PI 567516C crosses, respectively, and grown in two Missouri environments in 2008. More than 900 simple sequence repeat (SSR) and single nucleotide polymorphism (SNP) markers were used for mapping in each population. Across environments and genetic backgrounds, we have identified seven QTL for protein, six for oil, and four for seed weight. Two QTL were detected in common for protein and oil, one on chromosome (Chr.) 5 and another on Chr. 6. Additionally, we have detected one new seed weight QTL on Chr. 6, in the same region of protein and oil QTL. Confirmed protein and oil QTL on Chrs. 5 and 6 may be important targets to find candidate genes involved in modification of protein and oil contents and seed weight using genetic and genomic approaches. Also, SSR and SNP markers closely associated with these QTL can be useful for marker‐assisted selection.